trigon 89 : "aktuelle" kunst. - Künstlerhaus, Graz (Graz : Neue Galerie am Landesmuseum Joanneum, 1989)
Cattani, Giorgio ; Kirchhoff, Thorsten ; Petercol, Goran ; Potrc, Marjetica ; Erjautz, Manfred ; die Firma ; Beaugrand, Catherine ; Hale, Mathew ; van den Toorn, Joost ; Perrin, Carmen ; Szalai, Tibor
trigon 89 : "aktuelle" kunst, steirischer herbst '89, Neue Galerie Künstlerhaus, Graz, 15.10. - 12.11.1989
kunstcatalogus